Bullying and behavioural conflict at work: the duality of individual rights - Barmes, Lizzie (Oxford, 2015)
"In an empirical study of the interaction between law, adjudication, and conflicts about behaviour in the workplace, Lizzie Barmes analyses how labour and equality rights operate in practice in the UK. Arguing that individual employment rights have a Janus-faced quality, simultaneously challenging and sustaining existing distributions of power between management and employees, she calls for legal intervention at work to focus on resolving tensions between collective and individual concerns across the range of workplaces, and to stimulate the expression and reconciliation of different viewpoints in the implementation and enforcement of individual legal entitlements.